Effect of Feeding Containing Hydro Vac Vaccine on The Total Red Blood Cell of Siamese Jambal Fish (Pangasius hypophthalmus) Kept in Cages - Nikmal Pane; Morina Riauwaty; Iesje Lukistyowati (Jurnal Akuakultur SEBATIN, 2021)
search was to determine the effect of feeding containing Hydrovac vaccine on the total of red blood cells in Siamese jambal fish (Pangasius hypophthalmus). This research was conducted in December 2019 – January 2020. The method was an experimental method with a Completely Randomized Design (CRD) one factor with four treatments level and three times replication, The treatments were P0: control (feed that does not contain HydroVac vaccine), P1: feed containing HydroVac at a dose 2 ml of vaccine, P2: feed containing HydroVac at a dose 3 ml of vaccine, P3: feed containing HydroVac at a dose 4 ml of vaccine, each treatment dose was diluted with 100 ml distilled water/Kg of feed. The test fish used were the Siamese jambal fish seeds size 8-12 cm. The result shown that the total erythrocyte, hematocryte value, hemoglobin level, absolute weight growth, relative percent survival (RPS) and water quality. The research showed that the best treatment was the giving of vaccine with dose of 4 ml seen from the average eritrocite rate 166.6969x104 sel/mm3, hematocrit value 37.43%, hemoglobin 8.66 g/dL, relatif percent survival (RPS) 56,25 %, beyond life 95,33 % and water quality, temperature range between 28-290C, pH 6, DO 7 and ammonia 0,05 ppm.